Antioxidative Capacity of Soyfoods and Soy Active Compounds - Wanida Tewaruth Chitisankul; Kazuko Shimada; Chigen Tsukamoto (Polish Journal of Food and Nutrition Sciences)
Soyfood isoflavones and soyasaponins are effective compounds in terms of their health-promoting properties. Their chemical structure plays an important role in their antioxidative activity. Thus, six isoflavones and four soyasaponins that are targeted in soyfood were evaluated for their peroxyl radical scavenging capacities by the hydrophilic-oxygen radical absorbance capacity (H-ORAC) method. The antioxidant capacity of non-fermented and fermented soyfoods was also determined by the same method. The results revealed that isoflavones showed higher peroxyl radical scavenging capacities than soyasaponin, with their activities found to depend on their chemical structure. The aglycone isoflavones promoted higher H-ORAC values than glycoside and malonyl glycoside isoflavones, respectively. On the other hand, DDMP saponin promoted a higher H-ORAC value than its derived compound, group B saponin, and the aglycone soyasaponin. In the case of soyfoods, fermented soyfoods had higher antioxidative capacity that the non-fermented ones, especially the long-term fermented products. Soybean-koji miso presented the highest H-ORAC value, followed by natto, soy sauce, and tempeh. Moreover, lightness ( L* ) of miso and soy sauce showed a negative correlation with H-ORAC value probably due to browning substances which might derive from the amino-carbonyl reaction. Considering the high antioxidant capacity of fermented soyfoods, it might relate to aglycone isoflavones which promote strong radical scavenging capacity. Thus, fermented soyfoods, especially miso and natto, could be considered as health-promoting foods.